Evaluation and analysis of two village level models for sweet sorghum cane processing in Ilocos Norte, Philippines (2013)
Two sweet sorghum cane processing systems consisting of a stationary cane mill (SCM) and a mobile cane mill (MCM) that became operational as a village-level sweet sorghum processing system in Ilocos Norte were evaluated. With SCM, the stalk crusher was permanently established in barangay Bungon, Batac Ilocos Norte as the central processing station (CPS). Harvested stalks were hauled by trucks from production sites to the CPS for processing. For the MCM model, a reconditioned jeep carries the crusher to the plantation sites where stalks are crushed. Extracted juices were hauled to the CPS for processing. Cost wise, MCM is 100,000 more expensive than SCM (150,000) due to the cost of the jeep. The stakeholders had high confidence that the two village level cane mill system could fastrack sweet sorghum processing into a desired product which could translate to income generation and profitability. The advantages of SCM over MCM are the lower energy cost and lower biomass fuel cost of pasteurization due to the 80% bagasse component of fuel. With the MCM, biomass weight loss due to the staging did not occur, and crushing efficiency (CE) and juice yield were greater by 5.15% and 309kg, respectively than the SCM. This must be due to the closer roller clearance in the MCM. The CE of a modified laboratory model (MLCM) was reported at 51.6% greater by 22.15% than the SCM (29.45%) and by 16.95% than the MCM (34.6%). Such factors should be given particular consideration in the SCM or MCM to increase CE and make them more effective for village level sweet sorghum processing. If moved, the SCM and MCM system will be significant initiatives which could be replicated for use in sweet sorghum communities intending to indulge in the bioethanol industry.